Effect (love, respect, appreciation) to the student's educational achievement (An exploratory study in the schools of Baghdad governorate) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research discusses the problem of raising the scientific level of students by creating a leadership relationship between the student and the teacher governed by (love, respect, appreciation), and from here came the objectives of the research to test the relationship of influence between love, respect, appreciation and the scientific level of the student, and for that purpose a scheme was designed Hypothesis explains the nature of the relationship between its variables. In order to test the research hypotheses, it was applied based on a questionnaire that was designed to collect the required data. The sample size was 190 students in the sixth preparatory grade distributed among six different schools affiliated with the education of Baghdad / Karkh II. The effect relationship was tested using a set of statistical methods based on the statistical program (SPSS.V. 26).The research reached a set of conclusions, the most important of which is the existence of a positive statistically significant  effect between (love, respect, appreciation) and the Student's academic achievement.